Clinical and Technical Considerations for High Quality Breast MRI at 3 Tesla - Rahbar, Habib (J Magn Reson Imaging, 2013)
The use of breast MRI at 3 tesla (T) has increased in use substantially in recent years. Potential benefits of moving to higher field strength MRI include improved morphologic and kinetic assessment of breast lesions through higher spatial and temporal resolution dynamic contrast-enhanced MR examinations. Furthermore, higher field strength holds promise for the development of superior advanced breast MRI techniques, such as diffusion weighted imaging and MR spectroscopy. To fully realize the benefits of moving to 3T, a thorough understanding of the technical and safety challenges of higher field strength imaging specific to breast MRI is paramount. Through the use of advanced coil technology, parallel imaging, dual-source parallel radiofrequency excitation, and image-based shimming techniques, many of these limiting technical factors can be overcome to achieve high quality breast MRI at 3T.